Analysis of Milkfish Marketing in Ranooha Raya Village, Moramo District, South Konawe Regency - Mian Ida Parwati; Surni Surni; Muhammad Syukri (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2021)
The aims of this research are (1) to determine the marketing channels of milkfish; (2) to determine the level of marketing efficiency of milkfish. This research will be conducted from September to December 2020 in Raooha Raya Village, Moramo District, South Konawe Regency. Data collection techniques are by way of interviews—primary and secondary data. Data analysis is to determine the marketing channels of fish in the Moramo sub-district using descriptive analysis. The results showed that the marketing channel of milkfish in the village of Ranooha Raya consisted of 2 channels, namely marketing channel one from farmers- wholesalers- small traders- consumers, marketing channel two from farmers- small traders- consumers. Then the marketing margin of milkfish on channels I and II is the same, namely Rp. 2,000. The thing that causes the similarity of marketing margins for each channel is because, in Moramo District, farmers there determine the price where the price applies to each marketing agency.